Telling a different story of privilege and poverty : an intercultural Bible reading of Ruth in the context of contemporary South Africa - Naude, Stephanus Johannes (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.